AJCRỲ / COHPRÕ: dinâmicas de “espalhar” e “ajuntar” no território Krĩkati - CORREA, Kátia Núbia Ferreira (2016)
In this present thesis, I intend to understand the dynamics of Krĩkati mobility, taking the narrative of this people as reference, which concerns to the movements of “spreading” and “joining”. I take this dynamics as an axis to discuss the several meanings that Krĩkati people attribute to their ways of mobility inside their own territory, revealing their motivations to remain in a “big village”, and to “spread”, building “new” villages. Based on a five months field work, making use of direct observation, participations in events, informal talking, I intend to realize how Krĩkatipeople, classified as a Jê/timbira language speaker, make their interpersonal relations, and how they seek to make alternatives to the social structures to reach their goals. Starting from narratives which update the Aldeia Grande myth, I discuss how it has been (re)building the mobility e the Krĩkati relations against a demarcated land by the government, which impose limits to this mobility. When the Brazilian State demarcates the Krĩkati indigenous land, they ignore the dimensions of krikati territory, forcing them to (re) built their territoriality inside this space established as indigenous land. In this analyze, I aim to consider the mobility dynamics in the exercise context of domination/colonization exercised by the Brazilian state above the indigenous people, without discarding the native modes of reflexivity and creativity - of Krĩkati people - to occupy the land where it makes territory. I have highlighted the narratives of Krĩkati interlocutors, also making use of anthropological productions above this people and other Timbira people, as well the documents relatives to the demarcation process.